Eco inovação em materiais poliméricos: direcionadores e barreiras de pesquisas voltadas à eco inovação no Departamento de Engenharia de Materiais da Universidade Federal de São Carlos - Augusto, Edna Hercules (Universidade Federal de São Carlos, 2022)
Due to changes in contemporary capitalism, organizations are being forced to realize that for economic development to continue, they must seek innovations that maintain a balance with sustainability. Eco-innovations (EI) are inserted in this context, to the extent that they represent new products, processes, marketing techniques, or system-wide changes, whether disruptive or incremental, but always aimed at improving environmental performance. They are important for changing the current linear economic model, whose relationship with nature consists of extracting, producing, and disposing, to a circular economy model that intends to reconcile capital accumulation and environmental conservation. In this scenario, it is relevant to reflect on how the university is inserted into this EI system, since the knowledge produced therein places it in a role as a propeller of sustainable development. The understanding of drivers and barriers to EI(s) from the perspective of researchers at a Brazilian federal university can improve the management of innovation in the institution and its relationship with society. Thus, this dissertation aims to bring an analytical model of drivers and barriers to eco-innovations from the perspective of the university compared to that of companies whose vision was captured through systematic literature reviews (RBS) on eco innovation and key drivers and barriers, the state of the art has shown that this is a very incipient theme, with very few articles that bring the perspective of the university, This is a unique case study, but relevant because drivers and barriers of eco innovation activities are identified between 01/01/2010 and 01/12/2020, from the perception of researchers in polymeric materials of the Materials Engineering Department (DEMa) of the Federal University of São Carlos (UFSCar). This research has a qualitative nature and a descriptive and exploratory purpose, using content analysis techniques to codify and analyze data collected from documents and semi-structured interviews, helping the understanding of drivers and barriers to EI(s) from the perspective of researchers at a federal university, which can improve the management of innovation in the institution and its relationship with society
Eco innovation in polyimetric materials: drivers and barriers of research towards eco-innovation at the Materials Engineering Department of the Federal University of São Carlos
Keywords: Tipologia; Análise de conteúdo; Substituição de plásticos; Gestão da pesquisa; Gestão da inovação; Typology; Environmentally sustainable materials; Plastics substitution; Research management; Innovation management; CIENCIAS SOCIAIS APLICADAS::ADMINISTRACAO::ADMINISTRACAO PUBLICA::PLANEJAMENTO EM CIENCIA E TECNOLOGIA; CIENCIAS SOCIAIS APLICADAS::ADMINISTRACAO::ADMINISTRACAO PUBLICA; CIENCIAS SOCIAIS APLICADAS::ADMINISTRACAO